1998
DOI: 10.1002/(sici)1097-4547(19980901)53:5<613::aid-jnr11>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Uric acid protects neurons against excitotoxic and metabolic insults in cell culture, and against focal ischemic brain injury in vivo

Abstract: Uric acid is a well-known natural antioxidant present in fluids and tissues throughout the body. Oxyradical production and cellular calcium overload are believed to contribute to the damage and death of neurons that occurs following cerebral ischemia in victims of stroke. We now report that uric acid protects cultured rat hippocampal neurons against cell death induced by insults relevant to the pathogenesis of cerebral ischemia, including exposure to the excitatory amino acid glutamate and the metabolic poison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
195
1
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 316 publications
(215 citation statements)
references
References 66 publications
8
195
1
3
Order By: Relevance
“…By using complementary genetic approaches disrupting and overexpressing UOx, we have demonstrated that disruption of the UOx gene with a resultant rise in urate protects the nigrostriatal dopaminergic system, and conversely that transgenic overexpressson of UOx with a resultant fall in urate exacerbates dopaminergic neurodegeneration and resultant neurochemical and behavioral deficits in a 6-OHDA mouse model of PD. Neuroprotective effects of urate have been reported in various in vitro and in vivo experimental models of neurological disorders, including ischemic brain injury (13,14), multiple sclerosis (15), and spinal cord injury (16,17). However, evidence regarding urate in PD models is sparse and largely restricted to cellular models of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…By using complementary genetic approaches disrupting and overexpressing UOx, we have demonstrated that disruption of the UOx gene with a resultant rise in urate protects the nigrostriatal dopaminergic system, and conversely that transgenic overexpressson of UOx with a resultant fall in urate exacerbates dopaminergic neurodegeneration and resultant neurochemical and behavioral deficits in a 6-OHDA mouse model of PD. Neuroprotective effects of urate have been reported in various in vitro and in vivo experimental models of neurological disorders, including ischemic brain injury (13,14), multiple sclerosis (15), and spinal cord injury (16,17). However, evidence regarding urate in PD models is sparse and largely restricted to cellular models of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Urate protected cultured spinal cord neurons from glutamate toxicity [37] and was neuroprotective in models of spinal cord injury, multiple sclerosis, brain injury, and stroke [38][39][40][41]56]. This growing literature suggests a potential neuroprotective role for urate beyond PD.…”
Section: Urate Is Neuroprotective In Several Preclinical Models Of Nementioning
confidence: 99%
“…Neuroprotective [35] Neuroprotective in SCI, brain ischemia/stroke, MS [38][39][40][41] Clinical trials SURE-PD (phase II trial) [10] URICO-ICTUS (phase IIb/III trial in stroke) [42,43] PD = Parkinson's disease; ALS = amyotrophic lateral sclerosis; AD = Alzheimer's disease; HD = Huntington's disease; MSA = multiple system atrophy; MCI = mild cognitive impairment; SCI = spinal cord injury; MS = multiple sclerosis …”
Section: In Vivomentioning
confidence: 99%
“…Not only has evidence of peroxynitrite production been detected in spinal cord tissues from rats after traumatic injury (5-7), but administration of a peroxynitrite donor directly into the rat spinal cord has been shown to cause neuronal cell death and neurological deficit (8). In addition, a number of previous reports have demonstrated that peroxynitrite is toxic for neurons, including primary spinal cord neurons, and neuronal cell lines in vitro (9)(10)(11)(12)(13).…”
mentioning
confidence: 99%
“…[22][23][24], a neurodegenerative disease model. There is evidence that UA protects different neuronal cell populations from peroxynitrite-mediated toxicity (11,12). However, an additional aspect of the protective effect of UA in EAE is evidently directed at CNS inflammation, because UA treatment prevents the loss of blood-brain barrier (BBB) integrity that occurs in the disease, thereby inhibiting inflammatory cell infiltration (24)(25)(26)(27).…”
mentioning
confidence: 99%